2010
DOI: 10.1510/icvts.2010.242651
|View full text |Cite
|
Sign up to set email alerts
|

Azygos flap as a novel method for superior vena cava reconstruction

Abstract: In the surgical treatment of lung cancers invading the superior vena cava (SVC), primary closure is preferred for reconstruction when the resected area is small, but the repaired vessel can become constricted. A novel method for SVC repair with azygos flap, which is a longitudinally opened azygos arch, is a facile and effective treatment, and may prevent a reduction in the lumen if the area of tumor invasion is small and close to the azygos arch. When the azygos arch is not invaded by the tumor, this procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Therefore, if more extensive SVC wall resection is required, autologous pericardium is often used to cover the SVC defect [ 1 ]. Ohata et al recently reported another unique method with which to repair the SVC wall defects using an azygos flap [ 4 ]. They cut the azygos arch longitudinally on the caudal side to cover the SVC wall defect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if more extensive SVC wall resection is required, autologous pericardium is often used to cover the SVC defect [ 1 ]. Ohata et al recently reported another unique method with which to repair the SVC wall defects using an azygos flap [ 4 ]. They cut the azygos arch longitudinally on the caudal side to cover the SVC wall defect.…”
Section: Discussionmentioning
confidence: 99%